XC90 Plug-in Hybrid Customer Usage - Pipkorn, Linda (My University, 2018)
In order to meet present and future climate requirements, Volvo Car Corporation has announced that all passenger cars will be equipped with at least one electric machine by 2019. For the Transmission department, this change requires development of new concepts. To accurately predict loads on these new concepts, simulations and vehicle measurements require representative assumptions about how customers use their cars in reality. This can be achieved with so-called diagnostic readout (DRO) data, which is logged in cars and extracted at repair shops. This project has specifically focused on data related to hybrid-specific functionality. To facilitate readings and analysis of this type of data, a Python tool with an accompanying graphical interface was developed. The tool was then used to analyze the behavior of more than 12 000 XC90 T8 Plug-in hybrid customers world-wide. The average customers drive about one third of the distance electric (with combustion engine off). The Hybrid mode is used most frequently (more than 80 % of the time) and the Pure mode next most frequently. The average customer also spend more time driving in Sustain mode than in Depletion mode. In addition 56 % of the time is spent driving with a battery SoC below 35 % (the combustion engine can be used to charge the battery up to a SoC of 33 %). The Brake mode is used 12 % of the time and the vehicle speed distribution looks different for electric drive and drive with combustion engine on. A comparison between behavior of real customer population and the synthetic population used in the requirement setting procedure at the Transmission department pointed out following: the time spent in Pure mode and in Depletion mode are underestimated, but the time spent in Hybrid mode and the amount of electric drive are overestimated. Future work can use the results as a foundation for design of future transmission concepts. In addition it is recommended to establish a requirement setting procedure, based on simulations and vehicle measurements, which reduces the observed differences between synthetic and real customer population.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport